2021
DOI: 10.34172/jlms.2021.15
|View full text |Cite
|
Sign up to set email alerts
|

Blue Light Photodynamic Therapy With Curcumin and Riboflavin in the Management of Periodontitis: A Systematic Review

Abstract: Introduction: The aim of this article was to evaluate reports in the scientific literature that used antimicrobial photodynamic therapy (aPDT) with a blue light source and curcumin and riboflavin as photosensitizers in the management of periodontitis. Methods: The search was conducted in electronic databases, including PubMed, Web of Science, and Scopus, with the keywords "photodynamic therapy", "antimicrobial photodynamic therapy", "laser activated disinfection", "photoactivated disinfection", "light activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Essential oils of oregano (Origanum vulgare) are widely recognized for their antimicrobial activity, as well as their antiviral and antifungal properties. It is one of the most used aromatic plants, whose essential oils are particularly rich in mono- and sesquiterpenes [ 33 ]. In vitro studies of experimental gels with essential oils show anticariogenic and antibiofilm activities [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential oils of oregano (Origanum vulgare) are widely recognized for their antimicrobial activity, as well as their antiviral and antifungal properties. It is one of the most used aromatic plants, whose essential oils are particularly rich in mono- and sesquiterpenes [ 33 ]. In vitro studies of experimental gels with essential oils show anticariogenic and antibiofilm activities [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, curcumin used as photosensitizer activated by blue light in the aPDT procedure has the potential for reducing the bacterial count in periodontal infection. Etemadi et al states that several researchers have shown that curcuma as a photosensitizer activated by a blue wavelength is effective in the elimination of the various bacterial species involved in periodontal disease [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Shifting further to the right of the electromagnetic spectrum, we enter the visible light spectrum at the blue spectral regions (400–470 nm). Blue light, depending on the specific wavelength, may be absorbed by several photosensitizers, such as porphyrin/chlorophyll (405 nm) [ 69 ], curcumin (450 nm) [ 70 ], or even riboflavin (450–560 nm) [ 70 ] to generate ROS that can eliminate several pathogens. Blue light at 400–415 nm in itself has been shown to elicit significant antimicrobial effects without requiring exogenous photosensitizer ([ 43 ], see below; Section 2.2 ) and it has been explored in aPDT research.…”
Section: Light-based Anti-infective Agents: Can They Overcome Antimic...mentioning
confidence: 99%
“…Due to its hydrophobic behavior, the same changes in its structure including the production of nanocurcumin make it more applicable than its previous structure. It has a peak absorption in the blue range of electromagnetic wavelengths [24][25][26]. Méndez et al studied the effects of curcumin on total Streptococci, S. mutans, and total Lactobacilli biofilms, and reported that 600 µmol/L curcumin plus 75 J/cm 2 light-emitting diodes (LED) reduced significantly the vitality of intact biofilms.…”
Section: Application Of Natural Photosensitizers In Dental Cariesmentioning
confidence: 99%